2019
DOI: 10.1007/s10640-019-00331-0
|View full text |Cite
|
Sign up to set email alerts
|

Building Climate Coalitions on Preferential Free Trade Agreements

Abstract: In this paper, we discuss the endogenous formation of climate coalitions in the tradition of the issue-linkage literature. In particular, we propose a preferential free trade agreement on which a climate coalition should be built. The basic idea is that the benefits of free trade provide strong incentives for free riders to join the coalition. As a framework, a multi-stage strategic trade model is used in which a country may discourage greenhouse gas emissions by setting an emissions cap effective on a permit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In other scholar's opinion, greenhouse gas emissions can be reduced by incorporating trade restrictions without losing gains from multilateral trade cooperation (Barrett 2011). Regarding climate coalitions, Kuhn et al (2019) confirmed that emission reduction is higher, consumption patterns are more environmentally friendly, and coalition welfare is much more improved compared to the single-issued environmental agreements.…”
Section: The Role Of Trade Relations In Emissions Reductionsmentioning
confidence: 91%
See 1 more Smart Citation
“…In other scholar's opinion, greenhouse gas emissions can be reduced by incorporating trade restrictions without losing gains from multilateral trade cooperation (Barrett 2011). Regarding climate coalitions, Kuhn et al (2019) confirmed that emission reduction is higher, consumption patterns are more environmentally friendly, and coalition welfare is much more improved compared to the single-issued environmental agreements.…”
Section: The Role Of Trade Relations In Emissions Reductionsmentioning
confidence: 91%
“…If climate treaties are designed strategically, the threat to restrict trade will suffice to enforce an agreement (Barrett 2011). When a country's participation in joint emission reduction is higher, the consumption patterns are more environmentally friendly, and welfare is much more improved (Kuhn et al 2019). Considering the welfare effects of climate policy measures, when countries impose similar tariffs and barriers on environmentally friendly and polluting industries, global CO 2 emissions tend to fall, while incomes do not change (Shapiro 2020).…”
Section: Trade Liberalizationmentioning
confidence: 99%
“…The club's political utility hinges on its ability to provide "carrots", i.e., excludable benefits to members (Hovi et al, 2016). Such club goods can take different forms, with the two most prominent being preferential trade agreements (Kuhn et al, 2019) or other forms of cooperation, e.g., on research and development, innovation or industrial initiatives (Carraro, 2017). A club can also use "sticks", either coercing non-members to join or additionally increasing the advantage for existing members through sanctions (Nordhaus, 2015;Shaw and Fu, 2020).…”
Section: Cbam As a De Facto Climate Clubmentioning
confidence: 99%
“…In particular, when analyzing synergistic emission reduction among various regions within a country, cross-regional flows of goods and factors must be considered. Some studies have introduced trade models and new economic geography theories into game models to examine the relationships between carbon tariffs, trade barriers, and climate cooperation alliances [33][34][35]. These studies simulate and analyze cooperative behavior using assumed parameters, which cannot provide accurate characterizations of cooperative behavior based Land 2023, 12, 1723 3 of 23 on real data; however, they provide support for studying regional synergistic emission reduction from a trade perspective.…”
Section: Introductionmentioning
confidence: 99%